2017
DOI: 10.1071/mf16387
|View full text |Cite
|
Sign up to set email alerts
|

Lake and species specific patterns of non-diadromous recruitment in amphidromous fish: the importance of local recruitment and habitat requirements

Abstract: Understanding migratory life histories is critical for the effective management and conservation of migratory species. However, amphidromous migrations (fish hatch in streams, immediately migrate to the sea for a feeding period and return to fresh water as juveniles) remain understudied owing to the difficulties of tracking tiny larval fish. Despite this, it has widely been assumed that amphidromous fish have open, resilient populations, with marine-rearing larvae dispersing widely during their pelagic phase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…Consistent with previous studies in the Waipori–Taieri system (Closs et al, ; Hicks et al, ), we observed Ba signatures that remained high in otolith cores and low concentrations of Sr compared to diadromous common bully (Hicks, ), and we could not conclude that any fish were purely diadromous. We instead found continuous variation in Sr/Ca of both larval and adult otoliths, which we cautiously interpret as variation along a salinity gradient from estuarine to pure freshwater.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies in the Waipori–Taieri system (Closs et al, ; Hicks et al, ), we observed Ba signatures that remained high in otolith cores and low concentrations of Sr compared to diadromous common bully (Hicks, ), and we could not conclude that any fish were purely diadromous. We instead found continuous variation in Sr/Ca of both larval and adult otoliths, which we cautiously interpret as variation along a salinity gradient from estuarine to pure freshwater.…”
Section: Discussionsupporting
confidence: 89%
“…The underlying mechanism of carryover effects remains generally unknown, likely because it is tied to the complex series of events associated with development and metamorphosis. Several studies have revealed the role of genetic architecture which binds traits across life stages (Aguirre, Blows, & Marshall, 2014), while evidence for environment-specific covariations of genes across life stages (Gutteling et al, 2007) suggests that carryover effects are them- Consistent with previous studies in the Waipori-Taieri system (Closs et al, 2003;Hicks et al, 2017), we observed Ba signatures that remained high in otolith cores and low concentrations of Sr compared to diadromous common bully (Hicks, 2012), and we could not conclude that any fish were purely diadromous. We instead found continuous variation in Sr/Ca of both larval and adult otoliths, which we cautiously interpret as variation along a salinity gradient from estuarine to pure freshwater.…”
Section: Discussionsupporting
confidence: 77%
“…Raw data were baseline corrected and converted to element/Ca molar ratios using the Trace_Elements and Trace_Elements_IS data reduction schemes in iolite (Paton, Hellstrom, Paul, Woodhead, & Hergt, ). To characterize the rearing environment of each fish, the portion of the trace corresponding to the pelagic larval period of each otolith was isolated (Hicks et al, ), and the mean element/Ca molar ratios for this period were calculated. This period was determined based on the presence of a Mn spike indicating the core (Ruttenberg et al, ), and the rapid changes in several elements (particularly Sr and Ba) associated with recruitment‐related habitat switching (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…In New Zealand, amphidromy is considered to be the dominant strategy for around one‐third (about 10 species, excluding marine wanderers) of the indigenous fish fauna (McDowall, ), with newly hatched larvae carried downstream into the ocean by river flows before returning to fresh water as juveniles. Although the widespread dispersal of larvae has often been assumed (McDowall, ), patchy geographic distributions suggest that the larvae of some species, including crustaceans, (Morgan, Fisher, Miller, McAfee, & Largier, ) may have a greater degree of control over their distribution than first thought (Baker & Hicks, ; Hicks et al, ; Sorensen & Hobson, ; Warburton, Jarvis, & Closs, ; Yungnickel, ). Some researchers have suggested that passive larval dispersal away from natal habitats (passive dispersal hypothesis; Huey et al, ) may be an inherently risky strategy, and that although some dispersal undoubtedly occurs, remaining close to adult habitats (dispersal limitation hypothesis) may be preferable for some species, particularly those with specific adult habitat requirements (Hicks et al, ; Warburton et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation